Impact of Asian Dust Aerosol and Surface Albedo on Photosynthetically Active Radiation and Surface Radiative Balance in Dryland Ecosystems - X. Xi; I. N. Sokolik (Advances in Meteorology)
We investigated the extent to which Asian dust can affect vegetation in dryland ecosystems through altering photosynthetically active radiation (PAR) and shortwave and longwave radiation components of the surface energy balance. Results show that dust decreases the surface radiative balance and total PAR. The diffuse component of PAR, however, increases with increasing dust load but then decreases after reaching a maximum at a certain optimum condition. The forcing efficiency ranges from −67.7 to −82.2 Wm-2 τ0.5      −1 in total PAR and from −68.8 to −122.1 Wm-2 τ0.5      −1 in surface radiative balance. The ratio of total PAR to downwelling shortwave flux remains nearly constant (0.45±4%) similar to other aerosol types, while the ratio for the diffuse faction of PAR exhibits significant variations. The impact of dust on the gross photosynthetic rate varies among different types of crops. C4 plants such as corn tend to be less sensitive to the dust optical properties compared to C3 plants such as soybean and wheat.